1994
DOI: 10.1055/s-2008-1035554
|View full text |Cite
|
Sign up to set email alerts
|

Les métastases de I'uvée: étude statistique de 133 cas

Abstract: 133 cases of uveal metastasis were reviewed. The study included 97 women and 36 men, aged 10 to 80 (mean 53.1). Breast carcinoma in women and lung carcinoma in men were the primary malignancies, which most frequently led to uveal metastasis. Metastasis from lung carcinoma were often diagnosed before the primary tumor. Survival from ocular diagnosis to death depends on the histological type of the primary tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…For example 100% of patients with smaller tumors and without retinal detachment but only 30% of patients with larger tumors and a retinal detachment had an improvement of VA after RT [17]. The median survival time of all patients with choroidal metastases is short and ranges between 4-12 months [18,[27][28][29].This corresponds well with our results. It is widely accepted that breast cancer patients with choroidal metastases survive significantly longer than patients with other primary tumors [6,7,20].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For example 100% of patients with smaller tumors and without retinal detachment but only 30% of patients with larger tumors and a retinal detachment had an improvement of VA after RT [17]. The median survival time of all patients with choroidal metastases is short and ranges between 4-12 months [18,[27][28][29].This corresponds well with our results. It is widely accepted that breast cancer patients with choroidal metastases survive significantly longer than patients with other primary tumors [6,7,20].…”
Section: Discussionsupporting
confidence: 90%
“…So far described were cataract, keratopathy, retinopathy, neovascularisation of the iris, and opticus neuropathy [5,6,21,[34][35][36][37]. Typically neither the side effects are described in most publications nor is the good tolerance of the therapy emphasized [27,35,38]. One reason could be that 30-50% of the patients died after 5-7 months and therefore the late side effects did not appear.…”
Section: Discussionmentioning
confidence: 99%
“…Other similar classifications have been proposed [57,58]. Beati et al [6] noted among 133 patients, 73 of whom suffered from breast cancer, 97 cases (75%) with scotoma (16%). phosphenes (11%).…”
Section: Symptomatology According To the Location Of The Métastasésmentioning
confidence: 69%
“…Rarely, metastases will be found before the primary is located, when a breast cancer is found by further examination of the patient [4], Raymond et al [5] found that between 12 and 30% of the ocular metastases are the first sign in the evolution of breast cancer. In 6% of the patients of Beati et al [6], ophthal mologic metastases were the first sign of an unsuspected breast carcinoma. The metastases can be present simultaneously with the primary, but the large majority of the metastases occur af ter months or years, even decades.…”
Section: Mammakarzinom • Orbitalmetastasen • Metastasen Des Augesmentioning
confidence: 89%
See 1 more Smart Citation